Rhein kills Actinobacillus pleuropneumoniae, reduces biofilm formation, and effectively treats bacterial lung infections in mice - Ding, Haifeng; Bai, Yilin; Luo, Weiyu; Li, Hao; Zhu, Chunling; Zhao, Xueqin; Sun, Huarun; Wen, Yuliang; Zhang, Wei; Zhang, Shouping; Wen, Bo; Wang, Ruibiao; et al. (Journal of Medical Microbiology, 2024)
Background. Actinobacillus pleuropneumoniae, a member of the Pasteurellaceae family, is known for its highly infectious nature and is the primary causative agent of infectious pleuropneumonia in pigs. This disease poses a considerable threat to the global pig industry and leads to substantial economic losses due to reduced productivity, increased mortality rates, and the need for extensive veterinary care and treatment. Due to the emergence of multi-drug-resistant strains, Chinese herbal medicine is considered one of the best alternatives to antibiotics due to its unique mechanism of action and other properties. As a type of Chinese herbal medicine, Rhein has the advantages of a wide antibacterial spectrum and is less likely to develop drug resistance, which can perfectly solve the limitations of current antibacterial treatments. Methods. The killing effect of Rhein on A. pleuropneumoniae was detected by fluorescence quantification of differential expression changes of key genes, and scanning electron microscopy was used to observe the changes in A. pleuropneumoniae status after Rhein treatment. Establishing a mouse model to observe the treatment of Rhein after A. pleuropneumoniae infection. Results. Here, in this study, we found that Rhein had a good killing effect on A. pleuropneumoniae and that the MIC was 25 µg ml−1. After 3 h of action, Rhein (4×MIC) completely kills A. pleuropneumoniae and Rhein has good stability. In addition, the treatment with Rhein (1×MIC) significantly reduced the formation of bacterial biofilms. Therapeutic evaluation in a murine model showed that Rhein protects mice from A. pleuropneumoniae and relieves lung inflammation. Quantitative RT-PCR (Quantitative reverse transcription polymerase chain reaction is a molecular biology technique that combines both reverse transcription and polymerase chain reaction methods to quantitatively detect the amount of a specific RNA molecule) results showed that Rhein treatment significantly downregulated the expression of the IL-18 (Interleukin refers to a class of cytokines produced by white blood cells), TNF-α, p65 and p38 genes. Along with the downregulation of genes such as IL-18, it means that Rhein has an inhibitory effect on the expression of these genes, thereby reducing the activation of inflammatory cells and the production of inflammatory mediators. This helps reduce inflammation and protects tissue from further damage. Conclusions. This study reports the activity of Rhein against A. pleuropneumoniae and its mechanism, and reveals the ability of Rhein to treat A. pleuropneumoniae infection in mice, laying the foundation for the development of new drugs for bacterial infections.
Keywords: Actinobacillus pleuropneumoniae